Barium as Honorary Transition Metal in Action: Experimental and Theoretical Study of Ba(CO)+ and Ba(CO)−. Issue 15 (9th March 2018) - Wu, Xuan; Zhao, Lili; Jiang, Dandan; Fernández, Israel; Berger, Robert; Zhou, Mingfei; Frenking, Gernot
Abstract: Ba(CO) + and Ba(CO) − have been produced and isolated in a low‐temperature neon matrix. The observed C−O stretching wavenumber for Ba(CO) + of 1911.2 cm −1 is the most red‐shifted value measured for any metal carbonyl cations, indicating strong π backdonation of electron density from Ba + to CO. Quantum chemical calculations indicate that Ba(CO) + has a 2 Π reference state, which correlates with the 2 D(5d 1 ) excited state of Ba + that comprises significant Ba + (5dπ 1 )→CO(π* LUMO) backbonding, letting the Ba(CO) + complex behave like a conventional transition‐metal carbonyl. A bonding analysis shows that the π backdonation in Ba(CO) + is much stronger than the Ba + (5dσ /6s)←CO(HOMO) σ donation. The Ba + cation in the 2 D(5d 1 ) excited state is a donor rather than an acceptor. Covalent bonding in the radical anion Ba(CO) − takes place mainly through Ba(5dπ )←CO − (π* SOMO) π donation and Ba(5dσ /6s)←CO − (HOMO) σ donation. The most important valence functions at barium in Ba(CO) + cation and Ba(CO) − anion are the 5d orbitals. Abstract : The barium carbonyl complexes [Ba(CO)] + and [Ba(CO)] − have been spectroscopically characterized and show a highly unusual bonding situation. The alkaline‐earth metal barium behaves like a transition metal.